Large‐Scale Droughts Responsible for Dramatic Reductions of Terrestrial Net Carbon Uptake Over North America in 2011 and 2012. Issue 7 (7th July 2018) - He, Wei; Ju, Weimin; Schwalm, Christopher R.; Sippel, Sebastian; Wu, Xiaocui; He, Qiaoning; Song, Lian; Zhang, Chunhua; Li, Jing; Sitch, Stephen; Viovy, Nicolas; Friedlingstein, Pierre; et al.
Abstract: Recently, severe droughts that occurred in North America are likely to have impacted its terrestrial carbon sink. However, process‐based understanding of how meteorological conditions prior to the onset of drought, for instance warm or cold springs, affect drought‐induced carbon cycle effects remains scarce. Here we assess and compare the response of terrestrial carbon fluxes to summer droughts in 2011 and 2012 characterized by contrasting spring conditions. The analysis is based on a comprehensive ensemble of carbon cycle models, including FLUXCOM, TRENDY v5, SiBCASA, CarbonTracker Europe, and CarbonTracker, and emerging Earth observations. In 2011, large reductions of net ecosystem production (NEP; −0.24 ± 0.17 Pg C/year) are due to decreased gross primary production (−0.17 ± 0.18 Pg C/year) and slightly increased ecosystem respiration (+0.07 ± 0.17 Pg C/year). Conversely, in 2012, NEP reductions (−0.17 ± 0.25 Pg C/year) are attributed to a larger increase of ecosystem respiration (+0.48 ± 0.27 Pg C/year) than gross primary production (+0.31 ± 0.29 Pg C/year), induced predominantly by an extra warmer spring prior to summer drought. Two temperate ecoregions crops/agriculture and the grass/shrubs contribute largest to these reductions and also dominate the interannual variations of NEP during 2007–2014. Moreover, the warming spring compensated largely the negative carbon anomaly due to summer drought, consistent with earlier studies; however, the compensation occurred only in some specific ecoregions. Overall, our analysis offers a refined view on recent carbon cycle variability and extremes in North America. It corroborates earlier results but also highlights differences with respect to ecoregion‐specific carbon cycle responses to drought and heat. Key Points: Large NEP reductions in 2011 and 2012 are due to contrasting effects of GPP and Reco in the context of droughts Two temperate ecoregions crops/agriculture and grass/shrubs contributed largest to these reductions Compensation of drought‐induced carbon uptake reductions due to warm spring occurred only in some specific ecoregions